J Plant Pathol Microbiol 2019
DOI: 10.35248/2157-7471.19.10.483
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Stripe Rust Resistance in Ethiopian Durum Wheat by Phenotypic Screening and Kompetitive Allele Specific PCR (KASP) SNP Markers

Abstract: Stripe (Yellow) rust caused by Puccinia striiformis f.sp. tritici (Pst) is one of the most devastating diseases of wheat in the highlands of Ethiopia. Improved cultivars often lose their resistance due to occurrence of new virulent races which overcome the genes and make the cultivars out of production. Therefore, identification of new sources of resistance genes helps in battling yellow rust and maximizes wheat production in Ethiopia. In this study, 300 durum wheat lines (landraces & cultivars) were screened … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…In agreement to this, biotic and abiotic resistance/tolerance genes or genomic regions were identified in Ethiopian durum wheat landraces, e.g. resistance to biotic factors such as stripe rust resistance [ 75 ], adult plant resistance to leaf rust and stem rust [ 46 , 76 , 77 ], abiotic stress resistance such as aluminum tolerance [ 78 ] and terminal drought tolerance [ 23 ]. Therefore, Ethiopian durum wheat landraces may increase the rate of genetic gain if strategically included in wheat breeding programs.…”
Section: Discussionmentioning
confidence: 81%
“…In agreement to this, biotic and abiotic resistance/tolerance genes or genomic regions were identified in Ethiopian durum wheat landraces, e.g. resistance to biotic factors such as stripe rust resistance [ 75 ], adult plant resistance to leaf rust and stem rust [ 46 , 76 , 77 ], abiotic stress resistance such as aluminum tolerance [ 78 ] and terminal drought tolerance [ 23 ]. Therefore, Ethiopian durum wheat landraces may increase the rate of genetic gain if strategically included in wheat breeding programs.…”
Section: Discussionmentioning
confidence: 81%
“…As a follow-up investigation, the associated SNPs can be validated for their diagnostic values in an independent germplasm. Ethiopian durum landraces have been suggested as a good source of resistance to wheat rusts [44][45]. This has been supported by association studies on relatively small sized Ethiopian durum panels in limited study environments [17].…”
Section: Introductionmentioning
confidence: 91%
“…Ethiopian durum landraces have been suggested as a good source of resistance to wheat rusts [4445]. This has been supported by association studies on relatively small sized Ethiopian durum panels in limited study environments [17].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Many studies have been done on stripe rust resistance using GWAS and identi ed many QTLs controlling the resistance distributing across the whole genome [29][30][31]. In addition, many simple sequence repeats (SSR), sequence-Tagged site (STS), sequence-characterized ampli ed region (SCAR), diversity arrays technology (DArT), and Kompetitive allele-speci c PCR (KASP) markers have been reported as good markers for MAS for stripe rust resistance genes in wheat [32][33][34][35]. Furthermore, Maccaferri et al, (2015) reported association mapping of the resistance to the American race of P. striiformis using a world-wide collection of spring wheat genotyped by DArT markers.…”
Section: Introductionmentioning
confidence: 99%